Understanding Public Sctor Problems Affecting Uganda: A Depth Analysis of The Public Choice Theory - Gloria Nambassa; Dyah Mutiarin (Journal of Government and Politics (JGOP), 2024)
This study aims to identify and analyze the major problems affecting the Ugandan public sector through the lens of public choice theory. The research addresses the economic, political, social, and technological challenges that force government institutions to seek new ways to improve public sector performance. Despite various reforms initiated over the past 25 years, corruption, inefficiency, and inadequate service delivery remain pervasive issues. Corruption affects resource allocation and hinders development, while inefficiency is linked to a lack of skilled personnel, outdated infrastructure, and bureaucratic red tape. Shortcomings in service delivery, particularly in health and education, contribute to public dissatisfaction.Methodologically, this study employs a qualitative analysis of existing literature and government reports to assess the effectiveness of anti-corruption measures, capacity-building initiatives, technology adoption, and bureaucratic streamlining. The analysis reveals that while efforts to enhance transparency through digital platforms and establish anti-corruption units have been made, the impact of these reforms has been limited. This limitation is attributed to implementation challenges and resistance to the application of private sector techniques in the public sector.The study concludes that sustained progress in the Ugandan public sector requires ongoing commitment, comprehensive institutional reforms, and active community engagement to ensure effective governance and improved service provision.